Effect of different concentrations of sodium chloride and soy protein isolate with mono- and diglycerides/corn oil on physical properties and stability of w/o/w double emulsion. Issue 1 (July 2021) - Nahak, M H; Dirpan, A; Tawali, A B; Syarifuddin, A
Abstract: The successful fabrication of double emulsion is determined by the ingredients or the process. The aim of the study was to determine the effects of sodium chloride and soy protein isolate with addition of mono-and diglycerides/corn oil on physical and stability of emulsion. Model emulsions with different concentration of sodium chloride (0.5% and 1.5%) and soy protein isolate (1% and 3%) with addition of mono-and diglycerides/corn oil (ratio 1:1) were prepared. Physical properties and stability of double emulsion were characterized by viscosity, emulsion stability, pH, and color. The results showed that the stability of double emulsion was significantly affected (p < 0.05) by the interaction between sodium chloride and soy protein isolate, whereas pH and viscosity were affected only by the concentration of soy protein isolate. However, double emulsion containing 1.5% of sodium chloride and 3% of soy protein isolate (SPI) with addition of mono-and diglycerides/corn oil showed the highest stability in comparing with emulsion containing 0.5% of sodium chloride and 3% of SPI.